The use of mobile devices as assistive technology in resource-limited environments: access for learners with visual impairments in Kenya. - Foley, Alan R.; Masingila, Joanna O. (Disability & Rehabilitation: Assistive Technology, 2015)
Purpose: In this paper, the authors explore the use of mobile devices as assistive technology for students with visual impairments in resource-limited environments. This paper provides initial data and analysis from an ongoing project in Kenya using tablet devices to provide access to education and independence for university students with visual impairments in Kenya. Method: The project is a design-based research project in which we have developed and are refining a theoretically grounded intervention - a model for developing communities of practice to support the use of mobile technology as an assistive technology. We are collecting data to assess the efficacy and improve the model as well as inform the literature that has guided the design of the intervention. Results: In examining the impact of the use of mobile devices for the students with visual impairments, we found that the devices provide the students with (a) access to education, (b) the means to participate in everyday life and (c) the opportunity to create a community of practice. Conclusions: Findings from this project suggest that communities of practice are both a viable and a valuable approach for facilitating the diffusion and support of mobile devices as assistive technology for students with visual impairments in resource-limited environments.